CHALLENGES IN PUBLIC HEALTH PROGRAM PLANNING EXERCISE WITH A TEAM-BASED LEARNING APPROACH DURING COVID-19 CONFINEMENT - Putri, Nuzulul Kusuma (Universitas Gadjah Mada, 2023)
Background: Bachelor's Public Health program in Universitas Airlangga conducts the public health program planning course using a case-based that involves an interdisciplinary health workforce and community. Teams of students exercise the program planning cycle to design a health program.Aims: This paper describes the course structure based on the lesson study framework and analyzes any challenges to applying this approach during COVID-19 confinement in Indonesia.Case Discussion: Public Health Program Planning and Evaluation Course are compulsory for public health bachelor students in Indonesia. The learning outcome is the same for all public health institutions, but the course design depends on the school. In Universitas Airlangga, this course is conducted through three phases of team-based learning for fourteen weeks a semester. Due to the shifting from offline to fully online learning during the Pandemic, significant changes have been made in the team forming and type for student assignments. This adaptation covered not only the learning media but also the subject matter.Conclusion: The lecturers realized the significant limitation is sharing an authentic experience in conducting primary data collection during situational analysis. Otherwise, a more COVID-19 contextual setting also urges to be delivered since it greatly disrupts how a public health program is conducted in Indonesia.